DEVELOPMENT AND POETIC FEATURES OF MODERN UZBEK POETRY - Nazarov Oktam Jorayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The content of the article is devoted to the development stages of modern Uzbek poetry and the scientifically based theories of studying its poetic features. At the same time, the results of scientific research on odes are mentioned in the article. Poetic features, which are an important part of qasidas, are also highlighted on the basis of comparative analysis.